Association between dissatisfaction with body image and health-related physical fitness among adolescents Associação entre insatisfação com a imagem corporal e aptidão física relacionada à saúde em adolescentes - Claumann G.S.* (2019)
© 2019, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.The scope of this study was to estimate the prevalence of dissatisfaction with body image and verify the association between dissatisfaction with thinness or with overweight and health-related physical fitness components among adolescents. Participants included 1058 adolescents (570 girls and 488 boys), with mean age of 16.3 (±1.0) years. The investigated variables were dissatisfaction with body image (Figure Rating Scale), and health-related physical fitness: body fat (skin folds), muscle strength (handgrip strength) and cardiorespiratory fitness (mCAFT test). The association of body image and the health-related physical fitness variables was tested by Multinomial Regression analysis. The prevalence of body dissatisfaction was 75.2% (girls = 79.5%; boys = 70.3%). Girls and boys with high body fat were less likely to be dissatisfied with thinness and more likely to be dissatisfied with overweight. Those who needed to improve muscle strength and cardiorespiratory fitness were more likely to be dissatisfied with thinness and with overweight, respectively. In conclusion, physical fitness was associated with body image, with the adolescents with less healthy conditions of the components being more dissatisfied.